Black Phosphorus: 3D Chemical Cross‐Linking Structure of Black Phosphorus@CNTs Hybrid as a Promising Anode Material for Lithium Ion Batteries (Adv. Funct. Mater. 12/2020). (17th March 2020) - Zhang, Yupu; Wang, Lili; Xu, Hao; Cao, Junming; Chen, Duo; Han, Wei
Abstract : In article number 1909372, Lili Wang, Wei Han, and co‐workers develop a high‐performance lithium ion battery based on a black phosphorus@CNT hybrid with a 3D chemical cross‐linking structure. With its strong trapping, good affinity, structural stability, and high adsorption for polyphosphorus, the developed BP@CNT hybrid electrodes display high capacity, good electrical conductivity, and a stable cycle life.